Multivalent reuse of web data about temporary art exhibitions: The Exhibitium Project - Rodríguez-Ortega, Nuria; Pino-Díaz, José; Suárez, Juan Luis; Bailón-Moreno, Rafael (My University, 2016)
Our proposal aims to display the analysis techniques, methodologies as well as the most relevant results expected within the Exhibitium project framework (http://www.exhibitium.com). Awarded by the BBVA Foundation, the Exhibitium project is being developed by an international consortium of several research groups . Its main purpose is to build a comprehensive and structured data repository about temporary art exhibitions, captured from the web, to make them useful and reusable in various domains through open and interoperable data systems.
Reutilización y aprovechamiento multivalente de datos sobre exposiciones artísticas temporales: el proyecto Exhibitium
Keywords: Minería de datos; Arte -- Exposiciones; Digital Art History; Digital Humanities; Art exhibitions; Data-driven analysis